Matriks Peluang Transisi Fuzzy Time Series Markov Chain untuk Peramalan Kurs Riyal dengan Rupiah - iin aini fitri; dony permana (Journal of Mathematics UNP, 2019)
Abstract –Currency rates are one of important indicators in a contry’s ecomony. The value of a country’s currency always fluctuation in value against another country’s currency at any time. Data that used in this research are currency rates data between Riyal and Rupiah. It got from the official website of Bank Indonesia This research goal is to predict the currency rate between Riyal and Rupiah in the future with Markov Chain Fuzzy Time Series method.  The result of this research based on kurs data processing in the form of transition opportunities between state are the exchange rate on the first day there is an interval 1, then the probability of the next day the exchange rate is in the interval 1 is 0.8000 and the probability of the next day the exchange rate is in the interval 2 is 0.2000, while being at intervals 3,4,5,6,7,8 is 0, and so onKeywords: Currency  Rate, Forecasting, Fuzzy Time Series Markov Chain Method